Chromoblastomycosis caused by Rhinocladiella aquaspersa - González González, Gloria María; Rojas, O. Carolina; González, José G.; Kang, Yingqian; De Hoog, G.S. (2013)
A case of chromoblastomycosis of the hand caused by Rhinocladiella aquaspersa is described. The case was acquired locally in tropical Venezuela and was successfully treated with oral itraconazole. & 2013 The Authors. Published by Elsevier B.V on behalf of International Society for Human and Animal Mycology